Navigating the complex path between the oxytocin receptor gene (OXTR) and cooperation: an endophenotype approach - Haas, Brian W.; Anderson, Ian W.; Smith, Jessica M. (Frontiers in Human Neuroscience, 2013)
Although cooperation represents a core facet of human social behavior there exists considerable variability across people in terms of the tendency to cooperate. One factor that may contribute to individual differences in cooperation is a key gene within the oxytocin system, the oxytocin reception gene (OXTR). In this article, we aim to bridge the gap between the OXTR gene and cooperation by using an endophenotype approach. We present evidence that the association between the OXTR gene and cooperation may in part be due to how the OXTR gene affects brain systems involved in emotion recognition, empathy/theory of mind, social communication and social reward seeking. There is evidence that the OXTR gene may influence the functional anatomy of the amygdala, visual cortex, anterior cingulate and superior temporal gyrus. However, it is currently unknown how the OXTR gene may be linked to the functional anatomy of other relevant brain regions that include the fusiform gyrus, superior temporal sulcus, ventromedial prefrontal cortex, temporoparietal junction and nucleus accumbens. We conclude by highlighting potential future research directions that may elucidate the path between OXTR and complex behaviors such as cooperation.